The Spatial Distributionof Tourist Sites in Samosir, North Sumatera - Sugiharto, Sugiharto; Delita, Fitra; Sidauruk, Tumiar (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The spatial distributions of tourist sites is one of basic components to formulating the tourism development policy based on their characteristics and promote tourist sites. GIS technology very helpfull to develop many kinds of sectors including tourism sectors. This research aims to map the distribution of tourist sites in Samosir District. The data used are compiled from observation and survey. Furthermore, the data were analyzed using Arc GIS software to obtain the map of tourist sites in Samosir District. The results reveals that almost 75 tourist attractions spread in 9 subdistricts in Samosir. Distribution of most sites is located mostly in the subdistrict of Simanindo and least in Sitiotio District. Tourism supporting infrastructure facilities such as hotels and other accommodations are also most in Simanindo District.